Under pressure – The working situation of Swedish healthcare managers during the first wave of COVID-19 - Björk, Lisa; Corin, Linda; Akerstrom, Magnus; Jonsdottir, Ingibjörg H.; Innocenti, Alessio Degl; Wijk, Helle; Ahlstrom, Linda (Frontiers in Psychology, 2023)
The aim of this study is to provide insight into the psychosocial work situation of hospital managers during the first wave of the COVID-19 pandemic. Mixed-effect modelling was used on survey data on job demands, job resources, job motivation and work-life balance among over 500 managers working in 55 departments of a large Swedish university hospital in 2019 and 2020. Responses from 6011 employees were then used to stratify the analysis for COVID-19 exposure. Inductive content analysis was applied to open-ended questions on the managers’ views on organisational prerequisites during the onset of the pandemic. The proportion of managers reporting difficulties with role clarity, quantitative demands, decision-making authority, emotional support, time for recovery at work, motivation deficits or problems with work-life balance clearly increased during the first wave of the pandemic. The proportion of managers reporting negative responses was higher in departments with high COVID-19 exposure. The qualitative analysis shows that overall governance in terms of clear, fair and well-communicated routines, resource allocation and division of responsibilities constituted an important framework for managerial during the crisis. Firstline managers also required a mandate to re-organize their roles and their teams to successfully adapt to the situation. Organisational and social support were also important resources. This is the first study investigating health care managers’ work situation during the first wave of the COVID-19 pandemic in a Swedish context. As expected, it indicates an increasingly strained work situation during the crisis, but it also provides findings on organisational prerequisites that allow health care managers to cope with stressful situations. In line with previous research on organisational resilience, the study provides suggestions for how higher-level managers can act in order to provide front-line managers with the organisational prerequisites they need to adapt, learn and develop successfully during times of unpredictability, insecurity and rapid change in order to offer the best possible support to health care workers.